2020
DOI: 10.1186/s12014-020-09295-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloride intracellular channel 4 participate in the protective effect of Ginkgolide B in MPP+ injured MN9D cells: insight from proteomic analysis

Abstract: Background: Ginkgolide B (GB), the extract of G. biloba leaves, has been shown to be protective against many neurological disorders, including Parkinson's disease (PD). Efforts have been made to synthesized ginkgolides analogs and derivatives with more targeted and smaller molecular weight. In the present study, four GB derivatives (GBHC-1-GBHC-4) were synthesized, and their protective roles in N-methyl-4-phenylpyridinium (MPP +) injured MN9D dopaminergic neuronal cell line were evaluated. Also, cell response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…CLIC4 played a critical function in maintaining mitochondrial membrane potential in L929 cells depleted of mitochondrial DNA ( 65 ). More recently, mitochondrial CLIC4 has been implicated in two human diseases, ethylmalonic encephalopathy ( 66 ) and Parkinson’s disease ( 67 ). We showed that in the absence of CLIC4, intracellular superoxide and H 2 O 2 levels were elevated, there was a high ROS environment, and cells were vulnerable to additional prooxidant exposures.…”
Section: Discussionmentioning
confidence: 99%
“…CLIC4 played a critical function in maintaining mitochondrial membrane potential in L929 cells depleted of mitochondrial DNA ( 65 ). More recently, mitochondrial CLIC4 has been implicated in two human diseases, ethylmalonic encephalopathy ( 66 ) and Parkinson’s disease ( 67 ). We showed that in the absence of CLIC4, intracellular superoxide and H 2 O 2 levels were elevated, there was a high ROS environment, and cells were vulnerable to additional prooxidant exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that ginkgolides and sesquiterpene protect mitochondria from age-related damage and improve mitochondrial function and energy metabolism [ 26 , 27 , 28 ]. There are two possible molecular mechanisms for mitochondrial protection: antagonism of platelet-activating factor receptor (PAF, 1-O-alkyl-2-acetyl-sn-glycerol-3-phosphocholine) [ 29 , 30 , 31 ] and chloride channels [ 32 , 33 , 34 ]. More than 30 genuine flavonoids are found in ginkgo biloba.…”
Section: Introductionmentioning
confidence: 99%